2018
DOI: 10.1017/s1368980018000447
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of underweight, overweight and obesity among a geriatric population living in a high-altitude region of rural Uttarakhand, India

Abstract: There is a need to develop and implement intervention strategies to prevent underweight, overweight and obesity among the geriatric population of India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 31 publications
2
27
0
1
Order By: Relevance
“…The district is situated at an altitude of 2084 m. The detailed sampling methodology undertaken for selection of the elderly subjects has been described in a previously published article. [8] A total of 1003 elderly population were enrolled from 30 clusters (villages) identified using population proportionate to size sampling methodology. Thirty elderly subjects in the age group of 60 years and above were selected from each cluster by house-to-house visit.…”
Section: Methodsmentioning
confidence: 99%
“…The district is situated at an altitude of 2084 m. The detailed sampling methodology undertaken for selection of the elderly subjects has been described in a previously published article. [8] A total of 1003 elderly population were enrolled from 30 clusters (villages) identified using population proportionate to size sampling methodology. Thirty elderly subjects in the age group of 60 years and above were selected from each cluster by house-to-house visit.…”
Section: Methodsmentioning
confidence: 99%
“…The published prevalence of obesity in older adults using BMI definitions that have been reported in the previous literature varies widely between geographical regions. For example, a recent published study in India among 981 adults aged 60 years and above found that 4.6% of the population fulfilled the BMI criteria for obesity [2] while Hajek et al found that 40.0% of the German population aged 75 years old and above exceeded the BMI cut-off for obesity [10]. more active and had higher determination in controlling their weight compared to the Western population based to explain the apparent discrepancy in levels of obesity among older adults between the two regions [11].…”
Section: Definition and Epidemiology Of Obesitymentioning
confidence: 99%
“…However, obesity in older adults are often underestimated due to the uncertainty of benefits over the risk of weight reduction programmed in older adults. Generally, it is widely accepted that obesity is often associated with multiple health conditions including type 2 diabetes mellitus, hypertension, sleep apnoea, hypercholesteremia, cancer [1,2] as well as several age-associated diseases such as osteoarthritis, dementia and cognitive impairment [3]. Additionally, some studies suggest that obesity may have an impact on falls in older adults, however, this relationship is not adequately established.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,4,5 WHO regards a BMI of less than 18.5 as underweight. 3,6 Obesity is a risk factor for a number of diseases which include high blood pressure, type 2 diabetes, chronic heart diseases, stroke, gall stones and osteoarthritis, poor outcomes of pregnancy and cancers. 4,[7][8][9] Factors which predispose people to obesity include genetic predisposition, ethnicity, gender, old age, high socioeconomic status, certain dietary behaviors such as consumption of red meat, high calorie diet, sedentary lifestyle and alcohol use.…”
Section: Introductionmentioning
confidence: 99%